SPECTRUM COMPILATION FOR VEHICLE ROAD SIMULATION TEST BASED ON TIME CORRELATED FATIGUE ANALYSIS WITH DAMAGE EDITING METHOD - HUA FeiFei; ZHENG SongLin; FENG JinZhi; YU JiaWei (Jixie qiangdu)
Vehicle road simulation test should reflect the vehicle service loads actually,traditional load spectrum compilation methods were unable to meet the requirements of road simulation test.Therefore it is necessary to apply a load spectrum compiling method which can retain characteristic of the service load.In this paper,Several kinds of load spectrum compiling methods are compared and analysized,and time correlated fatigue analysis with damage editing method is considered to be the most effective,because it can maintain all the properties of service load（ amplitude,frequency,loading sequence and multi-channel phase） over an accelerated time.Based on proving ground collected loading spectrum of the test vehicle,this method was applied to generate test spectrum.The effectiveness and validity of the accelerated spectrum were verified theoretically from amplitude domain and frequency domain.The results have shown that the test time of the accelerated spectrum was significantly reduced while simultaneously the damage value and properties of the original spectrum were well maintained.Finally,vehicle bench durability test was conducted,and the same test results have been acquired as those of field test.The validness of this methodology was demonstrated.